(untitled) (Journal of the College of Basic Education, 2022)
In recent years, the technique of magnetizing irrigation water has emerged to improve its properties, such as cracking salt crystals, increasing germination rates, improving saline soil conditions, early emergence, increasing soil water retention, and reducing surface tension. There are more than 14 properties that change in water after passing through the magnetic field, such as electrical conductivity and increased oxygen content. dissolved in water, increase the ability to dissolve salts, change the speed of chemical reactions, especially evaporation, and increase permeability. Magnetized water has the ability to wash out the salts in the soil and increase the readiness of nutrients in the soil.